Mode properties of telecom wavelength InP-based high-(Q/V) L4/3 photonic crystal cavities - Rickert, Lucas; Fritsch, Birk; Kors, Andrei; Reithmaier, Johann Peter; Benyoucef, Mohammed (Nanotechnology, 2020)
We present finite-difference time domain simulations and optical characterizations via micro-photoluminescence measurements of InP-based L4/3 photonic crystal cavities with embedded quantum dots (QDs) and designed for the M1 ground mode to be emitting at telecom C-band wavelengths. The simulated M1 Q-factor values exceed 106, while the M1 mode volume is found to be 0.33 × (λ/n)3, which is less than half the value of the M1 mode volume of a comparable L3 cavity. Low-temperature micro-photoluminescence measurements revealed experimental M1 Q-factor values on the order of 104 with emission wavelengths around 1.55 μm. Weak coupling behavior of the QD exciton line and the M1 ground mode was achieved via temperature-tuning experiments.<br
Keywords: photonic crystal; telecom wavelength; quantum dots; spectroscopy